2014
DOI: 10.4103/0970-1591.128497
|View full text |Cite
|
Sign up to set email alerts
|

Painful varicoceles: Role of varicocelectomy

Abstract: The incidence of varicocele in the general population is up to 15%. It is estimated that the prevalence of pain with varicoceles is around 2-10%. Till the year 2000, only two studies evaluated efficacy of varicocelectomy in painful varicoceles with conflicting results. Over the past decade many other studies have addressed this issue and reported on the treatment outcome and predictors of success. We critically appraised studies published from March 2000 to May 2013 evaluating surgical management in painful va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…We have outlined how varicoceles may be toxic to the testis, which could result in size difference, abnormal SA, or infertility Although it has been hypothesized that the varicocele adds weight to the scrotum causing tension on the spermatic cord leading to chronic, dull, aching testicular pain, the mechanism linking varicocele and testicular pain has yet to be elucidated 21 .…”
Section: Etiologymentioning
confidence: 99%
“…We have outlined how varicoceles may be toxic to the testis, which could result in size difference, abnormal SA, or infertility Although it has been hypothesized that the varicocele adds weight to the scrotum causing tension on the spermatic cord leading to chronic, dull, aching testicular pain, the mechanism linking varicocele and testicular pain has yet to be elucidated 21 .…”
Section: Etiologymentioning
confidence: 99%
“…Although one study grouped dull and dragging pain [13], and another study grouped dull and throbbing pain in the same category [15], most studies have shown www.wjmh.org a higher likelihood of pain resolution after surgery in varicocele patients complaining of preoperative dull pain than in those with other qualities of pain [7,14,16,17]. In line with these studies, some reviews and meta-analysis reported that the postoperative pain resolution rate was significantly higher when dull pain was experienced preoperatively [3,9,13]. The reason for the higher likelihood of postoperative pain resolution in patients with dull pain remains unclear.…”
Section: Discussionmentioning
confidence: 94%
“…The current surgical management of varicocoeles is largely focused on preventing or treating male infertility (Schlegel, 2012;Choi & Kim, 2013), with treatment of refractory orchialgia as a less common indication (Abrol et al, 2014). However for men without future reproductive intent, the absence of pain often leads to expectant management of varicocoeles rather than surgical repair although varicocoeles are recognized as progressive lesions (World Health Organization, 1992;Witt & Lipshultz, 1993).…”
Section: Discussionmentioning
confidence: 99%